Evaluation and Comparison of Electronic Learning and Traditional Education Methods in Terms of Practical Skills of Parametric Technicians in Prehospital Emergency Care - Mohsen Aminizadeh; Mohsen Aminizadeh; Amin Saberinia; Simin Kohan; Iraj Shokohi; Abolfalz Faghihi; Elaheh Aminizadeh (Kerman University of Medical Sciences, 2015)
Background & Objective: Advances in information and communication technology has created new attitudes toward education and its methods Thus changing learning approaches to training through the use of electronic resources and virtual education has become important The purpose of this study was to compare the two virtual and traditional education methods in terms of practical skills in prehospital emergency paramedic technicians   Methods: This quasiexperimental study was performed in 2013 Practical skills such as basic and advanced cardiopulmonary resuscitation triage and familiarity with emergency equipment and correct transference method were taught through workshops and electronic learning in two groups of 40 people Then learners satisfaction with the education methods was measured and data were analyzed using SPSS software   Results: The mean theory scores of all courses were significant There were significant differences between the mean scores of practical courses of cardiac and pulmonary resuscitation equipment and transference through workshops and electronic learning However no significant difference was observed among the two methods in triage training   Conclusion: According to the results the electronic learning method is recommended in courses such as triage that have more theoretical aspects for paramedic technicians Considering the characteristics of electronic learning it can be used as a complementary method to traditional education